Analysis of the Potential Topical Anti-Inflammatory Activity of Averrhoa carambola L. in Mice. (2nd May 2011) - Cabrini, Daniela Almeida; Moresco, Henrique Hunger; Imazu, Priscila; Silva, Cíntia Delai da; Pietrovski, Evelise Fernandes; Mendes, Daniel Augusto Gasparin Bueno; Prudente, Arthur da Silveira; Pizzolatti, Moacir Geraldo; Brighente, Inês Maria Costa; Otuki, Michel Fleith
Abstract : Inflammatory skin disorders, such as psoriasis and atopic dermatitis, are very common in the population; however, the treatments currently available are not well tolerated and are often ineffective. Averrhoa carambola L. (Oxalidaceae) is an Asian tree that has been used in traditional folk medicine in the treatment of several skin disorders. The present study evaluates the topical anti-inflammatory effects of the crude ethanolic extract of A. carambola leaves, its hexane, ethyl acetate, and butanol fractions and two isolated flavonoids on skin inflammation. Anti-inflammatory activity was measured using a croton oil-induced ear edema model of inflammation in mice. Topically applied ethanolic extract reduced edema in a dose-dependent manner, resulting in a maximum inhibition of 73 ± 3% and an ID50 value of 0.05 (range: 0.02–0.13) mg/ear. Myeloperoxidase (MPO) activity was also inhibited by the extract, resulting in a maximum inhibition of 60 ± 6% (0.6 mg/ear). All of the fractions tested caused inhibition of edema formation and of MPO activity. Treatment with the ethyl acetate fraction was the most effective, resulting in inhibition levels of 75 ± 5 and 54 ± 8% for edema formation and MPO activity, respectively. However, treatment of mice with isolated compounds [apigenin-6- C - β -l -fucopyranoside and apigenin-6- C -(2 ″ - O - α -l -rhamnopyranosyl)- β -l -fucopyranoside] did not yield successful results. Apigenin-6- C -(2 ″ - O - α -l -rhamnopyranosyl)- β -l -fucopyranoside caused only a mild reduction in edema formation (28 ± 11%). Taken together, these preliminary results support the popular use of A. carambola as an anti-inflammatory agent and open up new possibilities for its use in skin disorders.